Proszę o rozwiązanie.​



Proszę O Rozwiązanie class=

Odpowiedź :

[tex]a) f(x)=3x^2-6\\\Delta=0^2-4*3*(-6)\\\Delta=0+72\\\Delta=72\\p=\frac{0}{6}=0\\q=\frac{-72}{12}=-6\\W(0; -6)\\a>0 - \text{ramiona skierowane w gore}\\[/tex]

f↓ dla x∈(-∞; 0)

f↑ dla x∈(0; ∞)

Zw = y ∈ <-6; ∞)

[tex]b) f(x)=3(x-4)^2\\a=3\\p=4\\q=0\\W(4; 0)\\[/tex]

f↓ dla x∈(-∞; 4)

f↑ dla x∈(4; ∞)

Zw = y∈<0; ∞)

[tex]c) f(x)=3(x+2)^2+5\\a=3\\p=-2\\q=5\\W(-2; 5)\\[/tex]

f↓ dla x∈(-∞; -2)

f↑ dla x∈(-2; ∞)

Zw = y∈<5; ∞)

[tex]d) f(x)=-5x^2+9\\a=-5 - \text{ ramiona paraboli skierowane w dol}\\\Delta=0^2-4*(-5)*9\\\Delta=0+180\\\Delta=180\\p=\frac{0}{-10}=0\\q=\frac{-180}{-20}=9\\W(0; 9)[/tex]

f↑ dla x∈(-∞; 0)

f↓ dla x∈(0; ∞)

Zw = y ∈ (-∞; 9>

[tex]e) f(x)=-5(x+8)^2\\a=-5\\p=-8\\q=0\\W(-8, 0)[/tex]

f↑ dla x∈(-∞; -8)

f↓ dla x∈(-8; ∞)

Zw = y ∈ (-∞; 0>

[tex]f) f(x)=-5(x-3)^2-2\\a=-5\\p=3\\q=-2\\W(3; -2)\\[/tex]

f↑ dla x∈(-∞; 3)

f↓ dla x∈(3; ∞)

Zw = y ∈ (-∞; -2>

[tex]g) f(x)=(2-x)^2+1\\f(x)=4-4x+x^2+1\\f(x)=x^2-4x+5\\\Delta=(-4)^2-4*1*5\\\Delta=16-20\\\Delta=-4\\p=\frac{4}{2}=2\\q=\frac{4}{4}=1\\W(2;1)\\a=1\\[/tex]

f↓ dla x∈(-∞; 2)

f↑ dla x∈(2; ∞)

Zw = y∈<1; ∞)

[tex]h) f(x)=4-\frac23(x-1)^2\\f(x)=-\frac23(x-1)^2+4\\a=-\frac23\\p=1\\q=4\\W(1; 4)[/tex]

f↑ dla x∈(-∞; 1)

f↓ dla x∈(1; ∞)

Zw = y∈(-∞; 4>

[tex]i) f(x)=(3+x)^2-\sqrt2\\f(x)=9+6x+x^2-\sqrt2\\f(x)=x^2+6x+9-\sqrt2\\\Delta=36-4*1*(9-\sqrt2)\\\Delta=36-4(9-\sqrt2)\\\Delta=36-36+4\sqrt2\\\Delta=4\sqrt2\\p=\frac{-6}{2}=-3\\q=\frac{-4\sqrt2}{4}=-\sqrt2\\W=(-3; -\sqrt2)\\a=1[/tex]

f↓ dla x∈(-∞; -3)

f↑ dla x∈(-3; ∞)

Zw=y∈<-√2; ∞)